Upgrading the nutritional value of rice bran by Solid-State fermentation with pleurotus sapidus - Omarini, Alejandra Beatriz (2019)
Solid-state fermentation (SSF) of rice bran (RB) employing the edible fungus Pleurotus sapidus was investigated as a process strategy to improve the nutritional quality of this low-cost and abundant substrate. During fermentation, samples were withdrawn at different time intervals (4, 6, and 10 days) and further analyzed. Established methods were deployed to monitor the changes in nutritional composition (carbohydrates, proteins, ash, and lipids). Additionally, changes in fatty acid composition was studied as a function of culture progress. Results showed that the SSF of rice bran increased total carbohydrates from 36.6% to 50.2%, total proteins from 7.4% to 12.8%, and ash from 7.6% to 11.5%. However, the total lipid content was reduced from 48.5% to 27.8%. The fatty acid (FA) composition of RB included mainly oleic, linoleic, and palmitic acids. Upon fermentation with P. sapidus, small differences were found: linoleic acid and oleic acid content were increased by 0.4% and 1.1%, respectively, while palmitic acid content was reduced by 0.8%. This study demonstrated an improvement in the nutritional quality of RB after fermentation with P. sapidus, since protein, carbohydrates, minerals, and specific FA components were increased. As a whole, our results indicate that fermented rice bran could be used as a high-quality animal feed supplement.